Analysis of Service Factors that Influence the Bed Occupancy Rate in the Inpatient Room of Royal Prima Medan General Hospital - Wiwin Dwi Handayani; Tan Suyono; Sri Lestari Nasution; Ermi Girsang (International Journal of Health and Pharmaceutical (IJHP), 2022)
The government has a responsibility to ensure that every citizen gets health services. Minimum Service Standards Indicators aim to be a benchmark of achievement in hospital performance. The indicator that is often used is the Bed Occupancy Rate (BOR). The state of the inpatient installation is an internal determinant of increasing satisfaction from consumers (patients). The aim of the research is to help local governments to improve the level of public health. As well as helping Royal Prima General Hospital Medan provide the best health services, and high quality standards. This research is a quantitative analytical-observational study with a cross sectional approach. Performed at the private public hospital Royal Prima Medan. Primary and secondary data collection was carried out in March-May 2021. Data analysis used a quantitative analysis approach; Data editing, data coding, univariate analysis, bivariate analysis.This analysis was carried out by using the Analysis of Variance (ANOVA) test on the program IBM SPSS. The research subjects came from inpatient room respondents from grades 1, 2, and 3. Based on the results of the study, the attitude of medical personnel was significant (P=0.04) towards services. Medical and medical services were not significant (P=0.13) on health services. Public facilities and infrastructure are significant (P=0.03) on health services. Distance and location of settlements are not significant (P=0.18) to health services. In conclusion, the attitude of medical personnel and public facilities affects the patient's interest. Meanwhile, distance, residential location, and medical services did not affect the patient's interest. Suggestions from this research are to improve the performance of medical personnel and hospital workers, by conducting training and training gradual coaching, to support more conducive health services at Royal Prima General Hospital Medan